2018
DOI: 10.1021/acs.jmedchem.8b01076
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Branched Peptide That Recognizes the Rev Response Element (RRE) RNA and Blocks HIV-1 Replication

Abstract: We synthesized and screened a unique 46,656-member library composed of unnatural amino acids that revealed several hits against RRE IIB RNA. Among the hit peptides identified, peptide 4A5 was found to be selective against competitor RNAs and inhibited HIV-1 Rev-RRE RNA interaction in cell culture in a p24 ELISA assay. Biophysical characterization in a ribonuclease protection assay suggested that 4A5 bound to the stem-loop region in RRE IIB while SHAPE MaP probing with 234 nt RRE RNA indicated additional intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 53 publications
(105 reference statements)
0
27
0
Order By: Relevance
“…These results were consistent from our previous work, indicating the loop and bulge in the RRE SL-IIB construct, especially the upper stem region, are essential for peptide binding. 22,24 In addition, 4B3 showed lower selectivity for RRE SL-IIB in the presence of TAR RNA as the K d against RRE IIB increased approximately 10-fold. Since both TAR and RRE RNAs share a small stem-loop with a consensus sequence UGGG, this unique structure of the RNA may be necessary for 4B3 binding.…”
Section: Selectivity Of Hit Branched Peptide 4b3 Toward Rre Iib Tertimentioning
confidence: 98%
See 2 more Smart Citations
“…These results were consistent from our previous work, indicating the loop and bulge in the RRE SL-IIB construct, especially the upper stem region, are essential for peptide binding. 22,24 In addition, 4B3 showed lower selectivity for RRE SL-IIB in the presence of TAR RNA as the K d against RRE IIB increased approximately 10-fold. Since both TAR and RRE RNAs share a small stem-loop with a consensus sequence UGGG, this unique structure of the RNA may be necessary for 4B3 binding.…”
Section: Selectivity Of Hit Branched Peptide 4b3 Toward Rre Iib Tertimentioning
confidence: 98%
“…21 We recently reported the high-throughput screening and characterization of a fourth generation branched peptide library that consisted solely of unnatural amino acids at all variable positions. 22 Each unnatural amino acid offers a unique mode of binding (electrostatic interaction, hydrogen bonding, pi stacking, etc) and include L-Guanidinoproline (L), Daminoproline (D), guanine peptide nucleic acid (G), lysine boronic acid (B) and 1naphthylalanine (N) ( Fig. 1A).…”
Section: Other Strategies Incorporate Metal Binding Linkers In the LImentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic effects are achieved through the regulation of RNA maturation, splicing, interference, translation and stabilisation. More possibilities of drug formats and therapeutic mechanisms have been discussed, including peptides [182], aptamers [183] and RNA editing with CRISPR-Cas13 [184]. Over the past five years, an increasing number of RNA-targeted drugs have been approved.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Support for branched peptides was provided by Bryson et al [76], whose on-bead screening of a 4000 molecule library identified ligands that spanned the bulge and apical loop of HIV-1 TAR RNA with binding affinities in the low micromolar range. Subsequently, to enhance selectivity/affinity Dai et al [77] synthesized a ~46,000 compound on-bead library of branched peptides composed of unnatural amino acids ( Figure 9B). These included L-guanidinoproline and D-aminoproline as electrostatic mimics of arginine and lysine, respectively, 1-naphthalene to promote π-π stacking with nucleobases and pyrazine which acts as a hydrogen bond donor/acceptor.…”
Section: Exploiting Rre Conformational Flexibility With Branched Peptmentioning
confidence: 99%